Strengthening ecological awareness through an Eco-Theology Seminar: A community engagement program - Edi Purwanto (Penamas: Journal of Community Service, 2026)
The global ecological crisis has become one of the most pressing challenges facing contemporary societies, including religious communities. However, ecological awareness within many churches and theological institutions remains relatively limited. This community engagement activity aimed to strengthen ecological awareness through an eco-theological educational approach. The program was conducted in the form of a seminar entitled Eco-Theology: Christian Faith and Ecological Responsibility, held at Gedung NOY 153, STT Victory, Cibubur, Indonesia, on 21 February 2026. Participants consisted of church leaders and theology students who are actively involved in theological education and church ministry, with a total of 45 participants involved in the program. The activity employed a participatory educational approach that integrated theological reflection, interactive discussions, and evaluation of participants’ understanding through pre-test and post-test assessments. The results showed a significant improvement in participants’ understanding of the ecological crisis, the biblical foundations of creation care, Christian ecological responsibility, and commitment to environmental stewardship, with an average increase of approximately 46.7% from pre-test to post-test scores. This program demonstrates that eco-theology education can serve as an effective strategy for cultivating ecological awareness and encouraging sustainable practices within theological education and Christian communities.